Pengaruh Model Pembelajaran Post Solution Posing terhadap Peningkatan Hasil Belajar Kimia Siswa - Nova Irawati Simatupang; Agelin Kristin (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2023)
This research aims to determine whether there is an increase and percentage increase in students chemistry learning outcomes by using the problem posing learning model of the post solution posing type. This research was an eksperiment research with the pretest – posttest control group design. The population of this research were all students of class X IPA Senior High School (SHS) Pusaka 1 semester II. The research sample consisted of two classes with a total sample of 55 which were selected by random sampling technique. The research instrument used was a test instrument with a number of 15 multiple choice questions. The analysis precondition test showed that the data were normally distributed sig (0.088) > 0.05 and homogeneous sig (0.345) > 0.05. The hypothesis test was carried out by parametric test using the t-test with a significance level of 0.05. Based on statistical test, the t-count value (3.608) > t-table (2,006) with a significant value of 0,001 < 0.005. Based on this data analysis of these data it can be concluded that there is a significant increase in strudent chemistry learning outcomes with n-gain score 0.76